Negative dissipation gradients in hysteretic materials. Issue 38 (16th September 2016) - Jaafar, Miriam; Iglesias-Freire, Óscar; García-Mochales, Pedro; Sáenz, Juan José; Asenjo, Agustina
Abstract : Counter-intuitive monotonical reduction of energy dissipation is observed as the tip–sample distance decreases. The sensing of hysteretic processes by means of mechanical methods is reported. Abstract : Measuring energy dissipation on the nanoscale is of great interest not only for nanomechanics but also to understand important energy transformation and loss mechanisms that determine the efficiency of energy of data storage devices. Fully understanding the magnetic dynamics and dissipation processes in nanomagnets is of major relevance for a number of basic and applied issues from magnetic recording to spin-based sensor devices to biomedical magnetic-based hyperthermia treatments. Here we present experimental evidence for a counter-intuitive monotonical reduction of energy dissipation as the interaction between two nanomagnets is enhanced. This behavior, which takes place when spins are parallel, can be understood in terms of hysteresis phenomena involved in the reorientation of these spins. The measured magnetic losses of about a few femtowatts are in agreement with quasi-static micromagnetic numerical simulations.